KESIAPAN PERBANKAN SYARI’AH DI INDONESIA DALAM PENERAPAN LIQUIDITY COVERAGE RATIO BASEL III - Dian Nuriyah Solissa (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2017)
Abstract2008 crisis was hypothetically to be an impact of particular condition in which banking around the countries had the high degree of leverage and decrease the bank capital quality. The other influencing factors are the quality of corporate governance and the quality of risk management. Having seen these challenges, Basel Committee on Banking Supervision (BCBS) published a document of “Basel III: Global Regulatory Framework for More Resilient Banks and Banking Systems” on Desember 2010 as the new initiation.The scopes of Basel III are, (1) Empowering the Global Capital Framework, (2) Recognizing the Global Liquidity. This research works on providing an implementation prospect of global liquidity standard to Indonesian Syariah Banking.The results show that the average of syariah banking LCR has only reached 51,6% that means there must be certain improvement to minimally reach 60% before January 2015 2015. Furthermore, the yearly growth of LCR which stands on 3,22% in average is claimed to be far from the yearly targeted increase whisch is 10%, Thus, this current study suggest syariah banking to put an effort by uplifting the HQLA using the funding strategy to absorb more deposits. Keywords: Basel III, Liquidity Coverage Ratio, Syariah banking